2010
DOI: 10.1002/ptr.3044
|View full text |Cite
|
Sign up to set email alerts
|

Hypotensive effect of aqueous saffron extract (Crocus sativus L.) and its constituents, safranal and crocin, in normotensive and hypertensive rats

Abstract: In this study, the effects of saffron (Crocus sativus) stigma aqueous extract and two active constituents, crocin and safranal, were investigated on blood pressure of normotensive and desoxycorticosterone acetate-induced hypertensive rats. Three doses of crocin (50, 100 and 200 mg/kg), safranal (0.25, 0.5 and 1 mg/kg) and the aqueous extract (2.5, 5 and 10 mg/kg) were administered intravenously in different groups of normotensive and hypertensive animals and their effects on mean arterial blood pressure (MABP)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
103
3
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 152 publications
(112 citation statements)
references
References 18 publications
4
103
3
2
Order By: Relevance
“…DOCA-salt induction was performed according to the method of Imenshahidi et al (2010) and Bankar et al (2011) with modification. Briefly, the rats were subcutaneously injected with DOCA (10 mg/kgBW, Sigma-Aldrich, St. Louis, MO, USA) twice a week and given 0.9% NaCl in drinking water ad libitum for six consecutive weeks (Imenshahidi et al, 2010;Bankar et al, 2011).…”
Section: Doca-salt Inductionmentioning
confidence: 99%
See 1 more Smart Citation
“…DOCA-salt induction was performed according to the method of Imenshahidi et al (2010) and Bankar et al (2011) with modification. Briefly, the rats were subcutaneously injected with DOCA (10 mg/kgBW, Sigma-Aldrich, St. Louis, MO, USA) twice a week and given 0.9% NaCl in drinking water ad libitum for six consecutive weeks (Imenshahidi et al, 2010;Bankar et al, 2011).…”
Section: Doca-salt Inductionmentioning
confidence: 99%
“…Briefly, the rats were subcutaneously injected with DOCA (10 mg/kgBW, Sigma-Aldrich, St. Louis, MO, USA) twice a week and given 0.9% NaCl in drinking water ad libitum for six consecutive weeks (Imenshahidi et al, 2010;Bankar et al, 2011).…”
Section: Doca-salt Inductionmentioning
confidence: 99%
“…Safranal possesses a wide range of properties such as being anti-oxidant [3,13], anti-inflammatory [9,14], antidiabetic [21,28], antiseizure [11,12,24], anxiolytic [6], anti-hypertensive [16], cytoprotective [4] and anti-carcinogenic [22]. In our previous research, safranal displayed obvious protective effects on brain injury induced by transient global cerebral ischemia in rats [10].…”
Section: Introductionmentioning
confidence: 99%
“…Administrations of 10 mg/kg of aqueous extract, 1 mg/kg of safranal and 200 mg/kg of crocin caused 60 ± 8.7, 50 ±5.2 and 51 ± 3.8 mmHg reductions in MABP, respectively. Accordingly, the aqueous extract of saffron stigma had hypotensive properties which appear to be attributable, in part, to the actions of two major constitutes of this plant, crocin and safranal, and safranal was more important than crocin for lowering the blood pressure of rats [115] The effects of saffron (Crocus sativus) stigma aqueous extract was studied on blood pressure of normotensive and desoxycorticosterone acetate (DOCA)-salt induced hypertensive rats. Five weeks administration of three doses saffron aqueous extract (10, 20 and 40 mg/Kg/day) and spironolactone (50 mg/Kg/day) in different groups of normotensive and hypertensive rats (at the end of 4 weeks treatment by DOCA-salt) showed that chronic administration of saffron aqueous extract reduced the MSBP in DOCA salt treated rats in a dose dependent manner.…”
Section: Crocus Sativusmentioning
confidence: 99%